Traditional taboos: informal and invisible protection of remaining patches of forest in Vhembe District in Limpopo, South Africa - Sinthumule, Ndidzulafhi Innocent (Frontiers in Conservation Science, 2024)
Since 1990, there has been a global decline in forest areas. Between 2010 and 2020, the greatest annual net loss of forests was on the African continent. Despite South African indigenous forests and trees being protected under the National Forests Act of 1998 (Act No. 84 of 1998), the country has also shown an increased annual net loss of forests. Although the Vhembe District Municipality in South Africa has lost forest owing to human-induced deforestation and other land use activities, sacred forests have not been affected. According to traditional beliefs, exploitation of such indigenous patches of sacred forests is taboo. This study aims to explore the role of taboos in the protection of the remaining patches of sacred forest. The study relies on data collected between December 2022 and December 2023. Semi-structured interviews were conducted with key informants (n = 61) and local communities in Tshidzivhe and Duthuni villages (n = 60).Observations were used as a further data collection tool. The interview questions were prepared to assess the role of taboos in the protection and management of sacred forests. Data collected through interviews were analysed using thematic content analysis, while field observations helped to corroborate the results from the interviews. The study identified two main taboosone that restricts entry into the sacred forests (i.e. preventing entry into the sacred forests, and harvesting, hunting and hiking in these areas), and another that prohibits noise or activities that disrespect sacred forests. The study found that believers and non-believers alike, for fear of retribution by the spirits, still obey these taboos and their related myths. This has allowed these areas to develop dense stands of closed-canopy evergreen forest that support more diverse flora and fauna than found in surrounding areas. Although sacred forests are not meant for biodiversity conservation, they offer opportunities to be integrated into global conservation targets of "30x30" and "Half-Earth" by 2030. They also offer the opportunity of serving as carbon sinks which is key to climate change mitigation. Recommendations for protecting sacred forests and associated taboos are drawn up based on these results.